Analisis Scaffolding dan Visualisasi dalam Penyajian Materi Vektor 3D pada Modul Matematika Peminatan kelas X KD 3.2 - Suwanto; Adam Rafli; Indah Ayu Ramadany; Nabila Azuhra; Nofa Nasywa Ramadhani; Syifa Eriza Nasution; Mukhtar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted to assess the quality of Scaffolding and visualization in the presentation of the Mathematics Module material for Grade X KD 3.2 regarding 3D vector material. The approach used in this research is a qualitative descriptive approach, which is carried out by analyzing the structure of the material, illustrations, example questions, and exercises provided in the module using content analysis techniques. The focus of the analysis conducted leads to several main aspects, including: (1) The sequence and form of Scaffolding presented as support in understanding the concept gradually, and (2) The effectiveness of visualization to help define and organize spatial vector data in space. This research resulted in a finding that the module has used Scaffolding with a tiered presentation of concepts, starting from the initial stage, namely the introduction of vector material in space to the stage of applying operations on vectors. However, on the other hand, it was also found that there are several stages of this Scaffolding that are not consistent, namely in the transition from examples to exercises which require a higher level of independence. Based on the visualization, the module utilizes spatial coordinate diagrams and vector arrow representations. However, some visuals lack detail in depicting orientation and depth in space, potentially leading to misconceptions among students. Overall, the module provides sufficient support for learning, but further strengthening of conceptual visualizations and more systematic Scaffolding is needed to optimally facilitate students' spatial thinking.